Correlation between test anxiety, speaker self-confidence and fear of negative evaluation in college students - Malobabić, Marina M.; Živković, Danijela Z.; Đorđević, Marija M.; Ranđelović, Nebojša M.; Mitić, Petar M.; Stanković, Aleksandra Z. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2018)
The aim of this study was to determine the correlation between speaker self-confidence, test anxiety and fear of negative evaluation in college students, as well as connection of these variables with self-assessment of the preparedness for exam and confidence in their knowledge. There were 221 students (male and female) that participated in the study. The authors applied following scales: Scale of speaker self-confidence, Scale of test anxiety, Scale of fear of negative evaluation, and sociodemographic questionnaire designed for this research (gender, age, college year, level of parental education), as well as self-assessment of preparedness for exam and self-assessment of the confidence in one`s own knowledge. The test was carried out during the examination period. The results of the study show that there is a significant correlation between confidence in one`s knowledge and test anxiety, readiness for exam and speaker anxiety, as well as test anxiety, speaker anxiety, and fear of negative assessment among tested students.
Keywords: negative evaluation; speaker self-confidence; Test Anxiety; anxiety